Will a High-Performance Finance Function Company Become a High Performance Organization? - Situmeang, Chandra; Hasyim, Diana; Sibarani , Choms G. G. T. (CV. Publikasi Indonesia, 2023)
Each company has a different performance and competitiveness from other companies. This performance determines their resilience to face various economic conditions, including economic contraction due to the Covid-19 pandemic. Various kinds of literature state that High-Performance Organizations (HPO) are related to their financial management performance. This study took a sample of 66 small and medium-sized companies in North Sumatra Province, Indonesia. We conclude that all High-Performance Organizations (HPO) factors strongly correlate with the High-Performance Finance Function (HPFF). Therefore, if a company wants to become an High-Performance Organizations company, it must also become an HPFF company. Therefore, we suggest that the top management of each company pays attention to the interrelated aspects of managing the financial function to improve or maintain the company's competitiveness. Another thing to note is the HPFF characteristics, namely